Democracy, Justice, and Equality in Ancient Greece Historical and Philosophical Perspectives (Philosophical Studies Series,, 2018)
The original essays in this volume discuss ideas relating to political justice, distributive justice and addressing inequalities. These issues were as vigorously debated at the height of ancient Greek democracy as they are in many democratic societies today. Through perspectives from ancient Greece, contributing authors address topics relating to democracy, equality, justice, and other public goods, and they critically examine both the ancient debates and their historical context. Readers will discover research on the lessening of economic inequality during the Athenian democracy, and consideration of Plato's critique of Greek participatory democracies. Early chapters look at Plato's proposals such as abolition of private property for the ruling classes and his ideal constitution. Other papers discuss Socrates or Aristotle's views that are particularly relevant to contemporary political and economic disputes about freedom, slavery, the status of women, and public education, to name a few. This thorough consideration of the ancient Greeks' work on democracy and equality will appeal to scholars and researchers of the history of philosophy, as well as those with an interest in political philosophy.